Heavy metals content in soil and welsh onion from Mesilou agricultural area Ranau Sabah - Sahibin Abd Rahim; Ng Siuw Sing; Diana Demiyah Mohd Hamdan; Nur Zaida Zahari; Hennie Fitria Wulandary Soehady Erfen; Junaidi Asis; Baba Musta (Faculty of Science and Natural Resources, 2021)
Heavy metals content in Allium Fistulosum, the Welsh onion and its’ substrates was carried out for Mesilou agricultural area, Ranau, Sabah. Heavy metals studied were As, Pb, Ni and Cr. Extraction of heavy metals from soil and plant part follow the standard procedure executed for metals extraction. The metals content in soils were high for Cr and Ni in Station 2, 3, 4 and 5, which was influenced by the presence of ultrabasic material in the soil. Despite the high content of Cr and Ni other heavy metals content in general hovers within the lower limit of maximum allowable concentration. All heavy metals concentration in plant were higher than the standard concentration.